2021
DOI: 10.1101/2021.10.23.21265402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severity of Illness Caused by Severe Acute Respiratory Syndrome Coronavirus 2 Variants of Concern in Children: A Single-Center Retrospective Cohort Study

Abstract: Background: Recent surges in coronavirus 2019 disease (COVID-19) is attributed to the emergence of more transmissible severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern (VOCs). However, the relative severity of SARS-CoV-2 VOCs in children is unknown. Methods: This retrospective single-center cohort study was performed at the Ann & Robert H. Lurie Childrens Hospital of Chicago, academic free-standing childrens hospital. We included all children 0-18 years-old diagnosed with C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…17-21 In two studies reporting on paediatric inpatients and outpatients one from Brazil and one from the USA, the overall hospitalisation rate as well as the ICU admission rate of children infected with the gamma variant was higher than for non-VOCs (Gamma vs. non-VOC: 28.3% vs. 24.9%. 47 , Gamma vs. non-VOC: 5.2% vs. 1.2% 48 ). 47,48 Severity of delta variant infection was compared with the pre-delta period (including periods where previous VOCs where predominant) in eight studies but the reported data were inconsistent, and differences in disease severity could not be assessed.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…17-21 In two studies reporting on paediatric inpatients and outpatients one from Brazil and one from the USA, the overall hospitalisation rate as well as the ICU admission rate of children infected with the gamma variant was higher than for non-VOCs (Gamma vs. non-VOC: 28.3% vs. 24.9%. 47 , Gamma vs. non-VOC: 5.2% vs. 1.2% 48 ). 47,48 Severity of delta variant infection was compared with the pre-delta period (including periods where previous VOCs where predominant) in eight studies but the reported data were inconsistent, and differences in disease severity could not be assessed.…”
Section: Resultsmentioning
confidence: 93%
“…A detailed comparison between studies was not possible owing to differences in study populations (community or health care setting), symptoms recorded and age groups reported. 14-18,20,22-24,27,31-33,35,36,38-40…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Edward et al reported that the Alpha variant (B.1.1.7) was not associated with severe COVID-19 in the pediatric population. 5 Brookman et al also suggested that the Alpha variant (B.1.1.7) did not cause a different clinical course than the original strain. 37 This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, variants of concerns (VOC) have emerged, among which may be variants that are associated with increased transmission, immune evasion, and worse clinical outcome. 5 One of these VOCs, Alpha variant/VOC 202012/01 (Pango lineage B.1.1.7), outcompeted other SARS-CoV-2 lineages in the United Kingdom after its appearance at the end of 2020 and has spread promptly throughout the world. 6 It began circulating in Turkey in early 2021.…”
Section: Introductionmentioning
confidence: 99%